The abduction eaudiobook - Grisham, John (Theodore Boone, 2011)
Book 2 in the thrilling young mystery series from internationally bestsellling author John Grisham When we last saw Theo Boone, he ensured that justice was served by uncovering evidence that kept a guilty man off of the streets. Hot off this high-profile murder trial, thirteen-year-old Theo is still dispensing legal advice to friends and teachers. But just when it seems as if his life has calmed down and gone back to the status quo, a new legal mystery comes to town, and this time it's personal.